Potential of the C Genome of the Different Variants of Brassica oleracea for Heterosis in Spring B. napus Canola - Nikzad, Azam; Kebede, Berisso; Pinzon, Jaime; Bhavikkumar, Jani; Wang, Xin; Yang, Rong-Cai; Rahman, Habibur (Frontiers in Plant Science, 2020)
The genetic base of Brassica napus canola need to be broadened for exploitation of heterosis at a greater level in the breeding of F1 hybrid canola cultivars. In this study, we evaluated 228 inbred B. napus canola lines derived from six B. napus × B. oleracea interspecific crosses and following two breeding methods (F2- and BC1-derived lines) to understand the effect of the B. oleracea alleles on heterosis for different agronomic and seed quality traits. Test hybrids of the inbreds derived from crosses involving vars. botrytis (cauliflower), alboglabra (Chinese kale) and capitata (cabbage) cv. Badger Shipper, on an average, gave about 10% mid-parent heterosis (MPH), and about 67% of the test hybrids gave higher seed yield than the common B. napus parent indicating that B. oleracea alleles can contribute to heterosis for seed yield in spring B. napus canola hybrids. This was also evident from a positive correlation of the genetic distance of the inbred lines from the common B. napus parent with MPH for seed yield (r = 0.31) as well as with hybrid yield (r = 0.26). In contrast, genetic distance showed almost no correlation with MPH as well as with test hybrid performance for seed oil and protein contents. The occurrence of positive correlation between seed yield of the inbred lines and test hybrids suggested the importance of the genes exerting additive effect for high seed yield in the hybrids. Very little or almost no heterosis was found for the other agronomic traits as well as for seed oil and protein content. While comparing the two breeding methods, no significant difference was found for seed yield of the test hybrids or the level of MPH; however, the BC1-derived inbred and test hybrid populations flowered and matured earlier and had longer grain-filling period than the F2-derived population. Thus, the results suggested that the B. oleracea gene pool can be used in the breeding of spring B. napus canola to improve seed yield in hybrid cultivars.